REDESIGN SPEAKING SYLLABUS BASED ON THE STUDENTS’ NEEDS AT BOSOWA UNIVERSITY - Rampeng Rampeng; Andi Hamzah Fansury; Hj. St Haliah Batau (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research is aimed to explore the students’ needs in learning speaking English and redesign the syllabus based on the students’ needs in order to improve the students’ skill in speaking English.The population of this research was the second semester students of English, Indonesian, Civic Education and Math Study Program in Faculty of Teacher Training and Education of Bosowa University Makassar in 2021/2022 Academic Year which consisted of 40 students.The result of students’ questionnaires and interviews indicate that redesign syllabus is a must to fulfill the students’ need to give impacts to students’ achievement in learning